Carotenoid profiling of yams: Clarity, comparisons and diversity. (1st September 2018) - Price, Elliott J.; Bhattacharjee, Ranjana; Lopez-Montes, Antonio; Fraser, Paul D.
Highlights: The carotenoid contents of elite accessions of yam ( Dioscorea spp.) have been determined. Accessions rich in tuber β-carotene provitamin A content have been identified. The data disprove the belief that yellow Guinea yams ( D. cayennensis ) have higher β-carotene content. The C25 -epoxy-apocarotenoid persicaxanthin has tentatively been identified. Abstract: Screening carotenoids of elite accessions of yam ( Dioscorea spp.) used in the global yam breeding program has been conducted to quantitatively determine the carotenoid composition of the crop. Comparisons to previous data reporting cerotenoid levels in yam has been made, in order to deduce greater perspectives across multiple studies. Characterisation of complex species and accession -specific profiles have shown a rich base of diversity that can inform breeding strategies. Key findings include; (i) the identification of accessions rich in β-carotene which can aid provitamin A biofortification, (ii) Data disputing the commonly held belief that yellow Guinea yam ( D. cayennensis ) has higher β-carotene content than that of white Guinea yam ( D. rotundata ), and (iii) the tentative identification of C25 -epoxy-apocarotenoid persicaxanthin with potential implications for tuber dormancy.